The Neoproterozoic Fiq glaciation and its aftermath, Huqf supergroup of Oman - Allen, P; Leather, J; Brasier, M (2004)
The < 1.5-km thick Fiq Member of the Ghadir Manqil Formation, Huqf Supergroup, Oman, contains a succession of Marinoan-age glacially and non- glacially influenced deposits overlain by a transgressive, 13C-depleted, deep-water dolostone (Hadash Formation) that deepens up into the marine shales and siltstones of the Masirah Bay Formation. The Fiq Member and Hadash-Masirah Bay Formations are well exposed in the core of the Jebel Akhdar of northern Oman and provide a valuable insight into the processes operating during a Neoproterozoic glacial epoch and its aftermath. The Fiq Member comprises seven stratigraphic units (F1-F7) of proximal and distal glacimarine, non-glacial sediment gravity flow, and non-glacial shallow marine facies associations. These units can be correlated over almost the entire Neoproterozoic outcrop belt (ca. 80 km) of the Jebel Akhdar. Four units contain glacimarine rainout diamictites, commonly at the top of cycles beneath strong lithofacies dislocations suggesting flooding. The units are thought to have been generated by combined glacio-isostatic and glacio-eustatic forcing caused by changing volumes of terrestrial glacier ice. The lateral persistence and thickness of massive diamictite units increase upwards in the stratigraphy, the youngest (F7) diamictite being abruptly overlain by the Hadash Formation. Correlation of lithofacies associations across the rift basin and palaeocurrents indicate that siliciclastic sediment and glacially entrained debris were derived from both basin margins. Open-water conditions existed during interglacials, attested to by the presence of wave-rippled sandstones in the western part of the basin. The Hadash carbonate also exhibits variations between east and west, showing that despite an overall deep-water depositional setting, rift margin and intrabasinal structure continued to exert a control on facies development during the post-glacial aftermath. Onlap of basin margins continued through the deposition of the Masirah Bay Formation. The sedimentology and stratigraphy of the Fiq Member and Hadash-Masirah Bay Formations have a number of implications for the Snowball Earth hypothesis. The overall stratigraphic evolution of the Fiq Member suggests a dynamic, temperate/polythermal style of glaciation, perhaps nucleated on uplifted continental or rift margin topography, with marine-terminating glaciers. Some transgressions coupled to deglaciations within the Fiq glacial epoch were accompanied by minor deposition of carbonate. However, final deglaciation triggered the deposition of a <8-m thick, deep-water dolomite contaminated with siliciclastics, with a lithofacies assemblage still reflecting the underlying bathymetric template, followed by relatively deep marine shales and siltstones. The preservation of relatively deep marine Masirah Bay sediments above the Fiq basin margin suggests either tectonic collapse of the rift shoulder or, more likely, rapid eustatic rise accompanying deglaciation. © 2004 Blackwell Publishing Ltd.